Reinventando o urbano: práticas culturais nas periferias e direito à cidade - Clarice de Assis Libânio (2017)
In the context of Brazilian and worldwide urbanization and of the formation of contemporary metropolises, cities and urbanized regions present an uneven, hierarchical, exclusionary and segregating center-periphery model. Contrary to what might be supposed, urban growth has meant worsening poverty and inequality, including violations of human, social and civil rights. The favelas and metropolitan peripheries are places where the processes of socio-spatial segregation manifest themselves with greater intensity and where, in counterpoint, the population develops practices for daily survival and for overcoming the absence of the State and guaranteeing rights. Facing such a situation, the concept of the Right to the City, proposed by Henri Lefebvre in the late 1960s, is used to discuss its multiple dimensions. The cultural dimension of the right to the city is proposed to become central to confront socio-spatial segregation, as exemplified by practices developed in the urban peripheries - especially in Belo Horizonte and in the RMBH. It seeks to understand what can be the contribution of socio-cultural actions and projects to face the socio-spatial segregation, the emancipation of the peripheral populations, the realization of the right to the city and the reinvention of the urban as a place of meetings, exchanges and access to opportunities. It is also discussed, from the study of four concrete experiences, how culture and its practices generate transformations at the personal, social and micropolitical spheres. It is also raised the possibility of having a fourth level, related to the transformations in the territorial sphere, within the scope of the city or urban centrality itself. The main assumption is that the metropolitan peripheries are places for the reinvention of the city, regarding sociopolitical power and the construction of autonomous and creative solutions that may contribute to generate resilience, a fundamental trait for the capacity to transform the expoliation processes to which they are subject daily. This thesis intends to contribute to make visible these important processes that have been seen in the Brazilian peripheries in the last decades, regarding transformation through culture. It also launches challenges for new studies and for the implementation of projects and policies that, through cultural practices, may contribute to the social emancipation, to the creation and the strengthening of meeting places and of ludic and playful places and, in more specific lefebvrean terms, to the rescuing of the oeuvre and the right to the city.